Peran Human Relation dan Budaya Organisasi dalam Membentuk Etos Kerja Pegawai Sektor Publik - Yuliantoharinugroho; Wilis Fahlefi; Keysha Aurelia Ardiningtyas (LPPM Akademi Manajemen Administrasi Yogyakarta, 2026)
This study aims to analyze the effect of human relations and organizational culture on employee work ethic at the Department of Population Control, Family Planning, Women’s Empowerment, and Child Protection (DP3APPKB) of Bantul Regency. This research employed a quantitative approach with an explanatory research design. The population consisted of all employees of DP3APPKB Bantul (61 employees), and the study used a saturated sampling technique, in which the entire population served as the sample. Data were collected through questionnaires and analyzed using multiple linear regression in SPSS version 23. The results indicate that human relations have a significant effect on employee work ethic, although the relationship is negative. This finding suggests that excessively informal interpersonal relationships may reduce employee discipline and focus at work. Organizational culture, on the other hand, has a positive and significant effect on work ethic, indicating that the stronger the implementation of organizational values, the higher the employee work ethic. Furthermore, human relations and organizational culture simultaneously have a significant effect on employee work ethic. These findings imply that organizations need to strengthen organizational culture while maintaining professional interpersonal relationships to enhance employee work ethic and organizational performance.